2013
DOI: 10.1002/jbio.201300157
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational biospectroscopy coupled with multivariate analysis extracts potentially diagnostic features in blood plasma/serum of ovarian cancer patients

Abstract: Despite numerous advances in "omics" research, early detection of ovarian cancer still remains a challenge. The aim of this study was to determine whether attenuated total reflection Fourier-transform infrared (ATR-FTIR) or Raman spectroscopy could characterise alterations in the biomolecular signatures of human blood plasma/serum obtained from ovarian cancer patients compared to non-cancer controls. Blood samples isolated from ovarian cancer patients (n = 30) and healthy controls (n = 30) were analysed using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
70
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(72 citation statements)
references
References 53 publications
1
70
1
Order By: Relevance
“…5). This data set consisted of blood serum and plasma samples of patients with ovarian cancer or endometrial cancer ( n = 30 for both) and control patients without ovarian cancer ( n = 30) analyzed with ATR-FTIR spectroscopy (7 spectra per sample) 41,131 . The classification rate, defined as the average between sensitivity and specificity, was used as a classification performance measure to class patients on the basis of their disease status (i.e., ‘normal’ versus ‘cancer’).…”
Section: Anticipated Resultsmentioning
confidence: 99%
“…5). This data set consisted of blood serum and plasma samples of patients with ovarian cancer or endometrial cancer ( n = 30 for both) and control patients without ovarian cancer ( n = 30) analyzed with ATR-FTIR spectroscopy (7 spectra per sample) 41,131 . The classification rate, defined as the average between sensitivity and specificity, was used as a classification performance measure to class patients on the basis of their disease status (i.e., ‘normal’ versus ‘cancer’).…”
Section: Anticipated Resultsmentioning
confidence: 99%
“…The IR spectrum contains rich and specific information about the molecular composition of the human serum which, coupled to advanced multivariate analysis tools, could deliver accurate diagnostics. Recent systematic studies have demonstrated the potential of IR serum based diagnosis with different data mining approaches such as Principal Components Analysis (PCA), PCA coupled to Linear Discriminant Analysis (PCA-LDA), Random Forest or Support Vector Machine (SVM) [26][27][28][29][30] . However, the development of spectroscopic technologies with medical perspectives needs to align with clinical requirements to enable clinical translation of these promising technologies 31 .…”
Section: Introductionmentioning
confidence: 99%
“…Due to its high specificity Raman spectroscopy is a suitable and widely used method for a high number of analytical tasks [31][32][33][34][35][36]. However, the Raman-effect is a very weak scattering process.…”
Section: Introductionmentioning
confidence: 99%